THE UNIQUENESS OF ALOYSIUS PIERIS’ COVENANT CHRISTOLOGY IN LIGHT OF THE LATIN AMERICAN CHRISTOLOGICAL MODEL - Alex Nilantha, Don (Asian Horizons, 2017)
Aloysius Pieris SJ through “Covenant Christology” constructs a new Christological paradigm that expresses a unique contextually liberational understanding of Jesus’ life, message, ministry, His death and Resurrection (Christ-event). “Covenant Christology” not only exposes a fresh search for a contextually liberational image of Jesus Christ in Asia, but also serves as a ‘unique trend-setter’ to do Christology in context. Pieris’ liberational hermeneutics on Semitic biblical categories couched in panoramic realities provide a promising methodology to do Christology. This paper explores the uniqueness of Pierisian Christological model in critical conversation with the Latin American Christological model. It also suggests that how Pieris rethinks of a contextual Christological model which is biblically faithful, anthropologically reconcilable, linguistically meaningful and contextually expressible.